Patterns of Hemodialysis Catheter Dysfunction Defined According to National Kidney Foundation Guidelines As Blood Flow <300 mL/min - Robert I. Griffiths; Britt B. Newsome; Geoffrey A. Block; Robert J. Herbert; Mark D. Danese (International Journal of Nephrology, 2011)
Blood flow rate (BFR) <300 mL/min commonly is used to define hemodialysis catheter dysfunction and the need for interventions to prevent complications. The objective of this study was to describe patterns of unplanned BFR <300 mL/min during catheter hemodialysis using data from DaVita dialysis facilities and the United States Renal Data System. Patients were included if they received at least eight weeks of hemodialysis exclusively through a catheter between 08/04 and 12/06, and catheter hemodialysis was the first treatment modality following diagnosis of end-stage renal disease (first access), or it immediately followed at least one 30-day period of dialysis exclusively through a fistula or graft (replacement access). Actual BFR <300 mL/min despite a planned BFR ≥300 mL/min defined catheter dysfunction during each dialysis session. There were 3,364 patients, 268,363 catheter dialysis sessions, and 19,118 (7.1%) sessions with catheter dysfunction. Almost two-thirds of patients had ≥1 catheter dysfunction session, and 30% had ≥1 catheter dysfunction session per month. Patients with catheter as a replacement access had a higher rate of catheter dysfunction than those with a catheter as first access (hazard ratio: 1.13; 𝑃=0.04). Catheter dysfunction affects almost one-third of catheter dialysis patients each month and two-thirds overall.